Case Report: Triple gastro-colic fistula after percutaneous endoscopic gastrostomy placement - Pittacolo, Matteo; Brolese, Marco; Vittori, Arianna; Passeri, Daniele; Salvador, Renato; Valli, Valeria; Vallese, Lorenzo; Baldan, Nicola; Da Dalt, Gianfranco; Valmasoni, Michele; Friziero, Alberto (Frontiers in Surgery, 2025)
BackgroundPercutaneous endoscopic gastrostomy (PEG) is a widely accepted procedure for long-term enteral nutrition. Although generally safe, rare but life-threatening complications can occur. We report a unique case of a triple gastro-colic fistula, identified during an emergency surgical intervention after radiological replacement of a PEG one year following its initial placement.Case presentationAn 83-year-old man with Parkinson's-related dysphagia underwent PEG placement. One year later, following catheter occlusion, it was replaced radiologically. The next day, the patient developed abdominal pain and diarrhea, and imaging revealed catheter misplacement into the transverse colon. Surgical exploration identified three chronic and dehiscent fistulous tracts involving the stomach, transverse colon, and sigmoid colon. The patient was treated with colonic resection, gastric double-layer suture, and surgical gastrostomy. Recovery was uneventful and the patient was discharged on postoperative day eight.ConclusionThis is the first reported case of a triple gastro-colic fistula following PEG placement. The case highlights that early recognition and multidisciplinary management of PEG-related complications are crucial. Prompt diagnosis and the availability of a specific Acute Care Department are essential for the effective management of such complex scenarios.